Meta-Analysis the Effects of Obesity and Type 2 Diabetes Mellitus on Covid-19 Mortality - Oktaviana Kurniawati; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, 2021)
Background: COVID-19 is a disease caused by a new coronavirus called SARS-CoV-2. In more severe cases, COVID-19 can cause death. The most severe COVID-19 patient mortality is associated with underlying health conditions. The most common associated comorbidities are pulmonary disease, diabetes, obesity, and old age. However, the effects of obesity and T2DM disease on the 2019 coronavirus disease (COVID-19) pandemic are controversial. This study aims to analyze the magnitude of the influence of obesity and T2DM on COVID-19 mortality.Subjects and Method: This study uses a systematic review and meta-analysis research design. The time of the selected test results is between January 2020 to January 2021. The search for articles is carried out for 1 month. Research data was searched from databases: PubMed, Google Scholar, JAMA, Willey, and Science Direct. Using search keywords: (Type 2 diabetes mellitus OR diabetic) AND (mortality OR death) AND (COVID-19 /OR Coronavirus OR SARS-CoV-2) AND (